LANGUAGE LEARNING GAMES DEVELOPMENT BASED ON CURRICULUM 2013 - Mahayanti, Ni Wayan Surya; Suprianti, G.A.P.; Kusuma, I Putu Indra (Universitas Pendidikan Ganesha, 2017)
This research aimed at developing character based language learning games in teaching English which can be used by teacher of junior high school grade VII as an alternative activities in the classroom. This research is R&D which used the design from Sugiyono (2011). The data in this study were collected through in depth interview, observation, and questionnaire distribution for both teacher and students. Then the data gained were analyzed qualitatively as the basis to develop the games and manual. As the result, 3 character based language learning games are developed; they are Word Bricks, Race Words dan Snake and Signs games. Validation from experts has been conducted and the scores given indicate that the product designed can be categorized as good games and excellent manual. It is also found that the product developed is categorized as good games and manual based on teacherâs score. After the implementation, it is shown that the students are motivated in learning English by using games. Besides, it is also found that studentsâ characters are starting to emerge in students who played the games.